Detachment Activated CyPA/CD147 Induces Cancer Stem Cell Potential in Non-stem Breast Cancer Cells - Fan, Xinyu; Li, Ling (Frontiers in Cell and Developmental Biology, 2020)
Background: Cancer stem cells (CSCs), responsible for cancer metastasis and recurrence, are generated from non-CSCs after chemo-radiation therapy. This study investigated the induction of CSC potential in non-stem breast cancer cells and the underlying molecular mechanisms in detachment culture. Methods: Bulk breast cancer cells, or sorted non-CSCs and CSCs were cultured under an attached or detached condition to assess CSC numbers, ability to form tumor spheres, expression of stemness markers, and chemoresistance. Lentivirus carrying CD147 shRNA or cDNA was used to manipulate CD147 expression, while CD147 ligand recombinant cyclophilin A (CyPA) or its inhibitor was used to activate or inhibit CD147 signaling. Results: Detachment promoted anoikis resistance, chemoresistance, sphere formation, self-renewal, and expression of stemness markers in breast cancer cells. Detachment increased functional ALDH+ or CD44highCD24-/low CSCs, and induced CSC potential in ALDH- or CD44lowCD24high non-CSCs. Upon detachment, both CD147 expression and CyPA secretion were enhanced, and CyPA-CD147 activation mediated detachment induced CSC potential in non-CSCs via STAT3 signaling. Clinically, CD147 and pSTAT3 were highly co-expressed and correlated with poor overall survival and tumor recurrence in breast cancer patients. Conclusions: This study demonstrates that detachment induces the generation of CSCs from non-stem breast cancer cells via CyPA-CD147 signaling, indicating that targeting CD147 may serve as a potential novel therapeutic strategy for lethal metastatic breast cancer by eliminating induced CSCs.